2010
DOI: 10.1105/tpc.110.080069
|View full text |Cite
|
Sign up to set email alerts
|

The CRR1 Nutritional Copper Sensor in Chlamydomonas Contains Two Distinct Metal-Responsive Domains    

Abstract: Copper response regulator 1 (CRR1), an SBP-domain transcription factor, is a global regulator of nutritional copper signaling in Chlamydomonas reinhardtii and activates genes necessary during periods of copper deficiency. We localized Chlamydomonas CRR1 to the nucleus in mustard (Sinapis alba) seedlings, a location consistent with its function as a transcription factor. The Zn binding SBP domain of CRR1 binds copper ions in vitro. Cu(I) can replace Zn(II), but the Cu(II) form is unstable. The DNA binding activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
141
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 71 publications
(104 reference statements)
8
141
1
Order By: Relevance
“…These include C 2 H 2 -type zinc fingers in Zap1, MTF-1, and now Loz1 and a cysteine/histidinerich domain in AD1 from Zap1 (4,22). Deletion of a cysteinerich metallothionein-like domain from the copper-responsive regulator Crr1 in Chlamydomonas also leads to increased expression of genes required for zinc uptake and the hyperaccumulation of zinc, suggesting that this may be another type of zinc-sensing domain (25,26). Despite a growing number of eukaryotic zinc-responsive factors, it is largely unknown whether these factors sense changes in zinc levels through zinc ion binding or if they are indirectly regulated by zinc (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These include C 2 H 2 -type zinc fingers in Zap1, MTF-1, and now Loz1 and a cysteine/histidinerich domain in AD1 from Zap1 (4,22). Deletion of a cysteinerich metallothionein-like domain from the copper-responsive regulator Crr1 in Chlamydomonas also leads to increased expression of genes required for zinc uptake and the hyperaccumulation of zinc, suggesting that this may be another type of zinc-sensing domain (25,26). Despite a growing number of eukaryotic zinc-responsive factors, it is largely unknown whether these factors sense changes in zinc levels through zinc ion binding or if they are indirectly regulated by zinc (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The Cu economy or "metal switch" mechanism, originally discovered in the green alga Chlamydomonas reinhardtii, includes the downregulation of the expression of potentially redundant Cu proteins for the metabolic reutilization of cellular Cu reserves (Burkhead et al, 2009;Blaby-Haas and Merchant, 2017;Kropat et al, 2015;Ravet et al, 2011;Shahbaz et al, 2015). In Arabidopsis thaliana, both processes are controlled by a conserved transcription factor, SPL7 (SQUAMOSA PROMOTER BINDING PROTEIN LIKE7), a homolog of the algal Cu sensor, CRR1 (COPPER RESPONSE REGULATOR1) (Yamasaki et al, 2009;Bernal et al, 2012;GarciaMolina et al, 2014;Sommer et al, 2010;Kropat et al, 2005). Both transcription factors (TFs) regulate gene expression during Cu deficiency through binding to Cu deficiency-responsive elements (59-GTAC-39) in promoters of their targets (Sommer et al, 2010;Yamasaki et al, 2009;Quinn et al, 2000;Birkenbihl et al, 2005;Garcia-Molina et al, 2014;Kropat et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis thaliana, both processes are controlled by a conserved transcription factor, SPL7 (SQUAMOSA PROMOTER BINDING PROTEIN LIKE7), a homolog of the algal Cu sensor, CRR1 (COPPER RESPONSE REGULATOR1) (Yamasaki et al, 2009;Bernal et al, 2012;GarciaMolina et al, 2014;Sommer et al, 2010;Kropat et al, 2005). Both transcription factors (TFs) regulate gene expression during Cu deficiency through binding to Cu deficiency-responsive elements (59-GTAC-39) in promoters of their targets (Sommer et al, 2010;Yamasaki et al, 2009;Quinn et al, 2000;Birkenbihl et al, 2005;Garcia-Molina et al, 2014;Kropat et al, 2005). Recent transcriptome analyses revealed that SPL7 is required for the expression of the iron (Fe)/Cu reductase oxidases, FRO4 and FRO5, and several Cu transporters, including members of the copper transporter family, COPT1 and COPT2, that together constitute the high-affinity Cu uptake system (Bernal et al, 2012;Gayomba et al, 2013;Jung et al, 2012;Yamasaki et al, 2009;Jain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dark hypoxic cells were grown in TAP medium for 24 h in 1% air, 2% CO 2 , and 97% N 2 by bubbling before collection as described in Ref. 56. Cell density (number of cells per milliliter of culture) was determined with a hemocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…Metal, sulfur, and phosphorous contents were determined by inductively coupled plasma mass spectrometry on an Agilent 8800 Triple Quadrupole ICP-MS instrument, in comparison to an environmental calibration standard (Agilent 5183-4688), a sulfur (Inorganic Ventures CGS1), and phosphorus (Inorganic Ventures CGP1) standard, using 89 Y (the 89 isotope of the chemical element Yttrium) as an internal standard (Inorganic Ventures MSY-100PPM). The levels of all analytes were determined in MS/MS mode, where 63 Cu were measured directly using helium in the collision reaction cell, whereas 56 Fe was directly determined using H 2 as a cell gas. The average of 4 technical replicate measurements was used for each individual biological sample, the average variation between the technical replicate measurements was 1.1% for all analytes and never exceeded 5% for an individual sample.…”
Section: Methodsmentioning
confidence: 99%